2018
DOI: 10.1073/pnas.1715972115
|View full text |Cite
|
Sign up to set email alerts
|

TRPV1 channels and the progesterone receptor Sig-1R interact to regulate pain

Abstract: The Transient Receptor Potential Vanilloid 1 (TRPV1) ion channel is expressed in nociceptors where, when activated by chemical or thermal stimuli, it functions as an important transducer of painful and itch-related stimuli. Although the interaction of TRPV1 with proteins that regulate its function has been previously explored, their modulation by chaperones has not been elucidated, as is the case for other mammalian TRP channels. Here we show that TRPV1 physically interacts with the Sigma 1 Receptor (Sig-1R), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 75 publications
(89 reference statements)
5
69
0
Order By: Relevance
“…Upon application of progesterone, the interaction of Sig-1R with the channel is disrupted, resulting in the downregulation of plasma membrane TRPV1 expression and, consequently, in a decrease in capsaicin-induced nociceptive responses of sensory neurons. These results were confirmed in vivo for both males treated with a synthetic antagonist of Sig-1R and pregnant females where progesterone levels were elevated [56]. In line with these results Sig-1R knockout mice exhibited endurance to pain and mechanical allodynia induced by formalin and capsaicin, respectively [64,65].…”
Section: Trp Channel Interactorssupporting
confidence: 72%
See 2 more Smart Citations
“…Upon application of progesterone, the interaction of Sig-1R with the channel is disrupted, resulting in the downregulation of plasma membrane TRPV1 expression and, consequently, in a decrease in capsaicin-induced nociceptive responses of sensory neurons. These results were confirmed in vivo for both males treated with a synthetic antagonist of Sig-1R and pregnant females where progesterone levels were elevated [56]. In line with these results Sig-1R knockout mice exhibited endurance to pain and mechanical allodynia induced by formalin and capsaicin, respectively [64,65].…”
Section: Trp Channel Interactorssupporting
confidence: 72%
“…Many factors among which steroids act on the Sig-1R resulting in negative or positive effects on the function and plasma membrane expression of potassium, calcium, and TRP channels [54]. Sig-1R was described to interact with TRPV1, TRPA1, TRPM8 in calcium and ligand-dependent ways [55,56]. Sig-1R and calmodulin were shown to bind directly to cytosolic regions of these three TRPs, and that this binding increasing in the presence of calcium.…”
Section: Trp Channel Interactorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A brief survey of the literature reveals that when using σ 1 receptor ligands in cellular or biochemical assays, incubation times and temperatures vary from room temperature for 20 minutes 33 to 37 °C incubation for up to 72 hours 31 . Ligand concentrations are sometimes nearly 10,000-fold over K d [34][35][36] . Our data indicate that it can take 1.5 hours or longer to reach saturation at 37 °C, and at room temperature it can take nearly a day.…”
Section: Discussionmentioning
confidence: 99%
“…It has been also observed that gonadal oestradiol (E2) alters the sensation of pain through upregulation of vanilloid receptors 1 (TRPV1) that plays a critical role in triggering pain. An increase in progesterone seems to determine a down-regulation of TRPV1 receptors in the plasma membrane of sensory neurons, decreasing the perception of pain under physiological conditions like pregnancy [274]. In contrast, testosterone has been shown to play a key role in inhibiting the expression of TRPV1 at the sensory ganglion level in a model of chronic inflammatory pain induced in rats, thus confirming the presence of sex differences for neuropathic and/or chronic pain in both animals and humans.…”
Section: Sex Disparity In Pain Threshold and Feelingsmentioning
confidence: 83%